Evaluation method for Raman depolarization measurements including geometrical effects and polarization aberrations. (24th January 2013) - Schlösser, M.; James, T. M.; Fischer, S.; Lewis, R. J.; Bornschein, B.; Telle, H. H.
Abstract : In this article, we address the notoriously difficult problem to quantitatively link measured Raman depolarization values to theoretical polarizability tensor quantities, since quantum calculations do not incorporate experimental parameters. For this, we introduce a numerical model to calculate, for realistic experimental configurations, effective Raman line strength functions, Φ, which find their way into depolarization ratios, ρ . The model is based on interlinked integrations over the angles in the light collection path and a finite Raman source volume along the excitation laser beam. The model deals also with the conditional aperture parameters, associated with more than one optical component in the light collection path. Finally, we also can take into account polarization aberrations introduced by the sample cell windows. The procedure was fully tested for Raman depolarization spectra of selected hydrogen isotopologues. Distinct aspects affecting Raman depolarization data were validated, namely: (1) excitation polarization impurities; (2) extended Raman excitation volumes; (3) Raman light collection over finite solid angles; and (4) polarization aberrations introduced by optics in the light collection path. The correction of the experimental measurement data for the aforementioned effects resulted in depolarization ratios for the Q 1 ( J  " ) Raman lines of H2 and T2, which mostly differed by less than 5% from those obtained by quantum‐calculations. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A numerical model was developed to evaluate, for realistic experimental configurations, effective Raman line strength functions, Φ, and depolarization ratios, ρ. It is based on interlinked integrations over the angles in the light collection path and a finite Raman source volume along the excitation laser beam. The model can take into account polarization aberrations introduced by sample cell windows and can deal with more than one optical component in the light collection path and the associated di‐attenuation and retardance effects.